2008
DOI: 10.1007/s12010-008-8222-3
|View full text |Cite
|
Sign up to set email alerts
|

Vermicomposting of Solid Waste Generated from Leather Industries Using Epigeic Earthworm Eisenia foetida

Abstract: Animal fleshing (ANFL) generated as solid waste from tannery industries was vermicomposted using the epigeic earthworm Eisenia foetida. The mixing ratio of ANFL with cow dung and agricultural residues as feed mixtures was maintained to be 3:1:1 respectively during the vermicomposting experiments for 50 days. Vermicomposting resulted in the reduction of pH 6.74 and C:N ratio 15.5 compared to the control sample. A notable increase in earthworm biomass was also observed in the vermin bioreactor. The germination i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
34
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(47 citation statements)
references
References 24 publications
11
34
2
Order By: Relevance
“…TG analysis is generally performed in the temperature range of 30 to 1200°C under heating rate of 10°C/min. The pressure is always maintained at 101 kPa (kilopascal) (Ravindran et al 2008(Ravindran et al , 2013.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…TG analysis is generally performed in the temperature range of 30 to 1200°C under heating rate of 10°C/min. The pressure is always maintained at 101 kPa (kilopascal) (Ravindran et al 2008(Ravindran et al , 2013.…”
Section: Methodsmentioning
confidence: 99%
“…Various researchers have used SEM technique to observe the changes in surface morphology of pre-and post-vermicomposted organic wastes (Ravindran et al 2008;Ravindran and Sekaran 2010;Zhao et al 2010;Li et al 2011;Unuofin and Mnkeni 2014;Lim et al 2014Kumar et al 2014;Rajpal et al 2014;Bhat et al 2014Bhat et al , 2015aWu 2015, 2016;Hussain et al 2016a). Ravindran et al (2008) recorded SEM to know the changes in surface morphology (texture) in the control and final vermicomposted mixtures of a solid waste (animal fleshing) produced from leather industry. The study observed that the aggregates of biomass was firmly bounded in the control animal fleshing mixture, whereas the lignin and the protein matrix was broken down by worms in the final feed mixtures of animal fleshing waste.…”
Section: Relevance and Use Of Sophisticated Techniques (Sem Ft-ir Tmentioning
confidence: 99%
“…In the final product the concentration of copper was significantly low (about 36.4% reduction was registered). Ravindran et al (2008) reported the vermicomposting of animal fleshing (ANFL) generated as solid waste from tannery industries using the epigeic earthworm Eisenia fetida. The mixing ratio of ANFL with cow dung and agricultural residues as feed mixtures was maintained at 3:1:1, respectively during the vermicomposting.…”
Section: Tanning Industry Wastementioning
confidence: 99%
“…Both delimed fleshings and residual hair might well constitute an important source of protein with interesting uses as biological fertilizers in agriculture or horticulture (Serrano et al 2003). Ravindran et al (2008) vermicomposted fleshings using the epigeic earthworm Eisenia foetida and used as nutrient-enriched products.…”
Section: Fleshing and Limed Split Wastesmentioning
confidence: 99%